FENOMENA PERUBAHAN MAKNA KATA BAHASA INDONESIA DALAM KONTEN PLATFORM INSTAGRAM DAN X - Ameylia Maya Kristinaupi; Nunung Sitaresmi; Lilis Siti Sulistyaningsih; Gibraltar Syawalan Gumilar; Iqssyzia Syahfitri (Jurnal Semantik, 2024)
On social media platform Instagram and X there is a phenomenon of changing the meaning of language. Changes in meaning include expansion, narrowing, complete transformation, refinement, and coarsening. Therefore, the authors conducted a study with the aim of investigating the phenomenon of semantic shifts occurring in social media in the digital era. The data for this study comes from Instagram and X. The dataset used in this study consists of Indonesian terms sourced from social media platforms that have undergone semantic shift. The methodology used by the researchers includes the use of listening and recording procedures. Through examination of the data and the debates that occurred, it was determined that there were five different categories of semantic shifts in the language use of Indonesian netizens on Instagram and X. The five categories of semantic shift are expansion, narrowing, coarsening, refining, and total change. The data results show that there are 17 words that experience changes in meaning. Among them, 3 words experienced a decline in meaning (dysphemia), 7 words experienced an expansion of meaning, 2 words experienced a narrowing change, 3 words experienced a complete change in meaning, and 2 words experienced a change to be more refined.